The back-to-back region in e+e- energy-energy correlation - de Florian, Daniel Enrique (2005)
We consider the back-to-back region in the energy-energy correlation in e+e- collisions. We present the explicit expression of the O (αS2) logarithmically enhanced contributions up to next-to-next-to-leading logarithmic accuracy. We study the impact of the results in a detailed comparison with precise LEP and SLC data. We find that, when hadronization effects are taken into account as is customarily done in QCD analysis in e+e- annihilations, the extracted value of αSMZ) is in good agreement with the current world average.